Oxytocin receptor agonist reduces perinatal brain damage by targeting microglia - Mairesse, Jérôme; Zinni, Manuela; Pansiot, Julien; Hassan‐Abdi, Rahma; Demene, Charlie; Colella, Marina; Charriaut‐Marlangue, Christiane; Rideau Batista Novais, Aline; Tanter, Mickael; Maccari, Stefania; Gressens, Pierre; Vaiman, Daniel; et al. (Glia, 2019)
Prematurity and fetal growth restriction (FGR) are frequent conditions associated with adverse neurocognitive outcomes. We have previously identified early deregulation of genes controlling neuroinflammation as a putative mechanism linking FGR and abnormal trajectory of the developing brain. While the oxytocin system was also found to be impaired following adverse perinatal events, its role in the modulation of neuroinflammation in the developing brain is still unknown. We used a double‐hit rat model of perinatal brain injury induced by gestational low protein diet (LPD) and potentiated by postnatal injections of subliminal doses of interleukin‐1β (IL1β) and a zebrafish model of neuroinflammation. Effects of the treatment with carbetocin, a selective, long lasting, and brain diffusible oxytocin receptor agonist, have been assessed using a combination of histological, molecular, and functional tools in vivo and in vitro. In the double‐hit model, white matter inflammation, deficient myelination, and behavioral deficits have been observed and the oxytocin system was impaired. Early postnatal supplementation with carbetocin alleviated microglial activation at both transcriptional and cellular levels and provided long‐term neuroprotection. The central anti‐inflammatory effects of carbetocin have been shown in vivo in rat pups and in a zebrafish model of early‐life neuroinflammation and reproduced in vitro on stimulated sorted primary microglial cell cultures from rats subjected to LPD. Carbetocin treatment was associated with beneficial effects on myelination, long‐term intrinsic brain connectivity and behavior. Targeting oxytocin signaling in the developing brain may be an effective approach to prevent neuroinflammation – induced brain damage of perinatal origin. Main Points A double‐hit insult model of perinatal brain injury reduced oxytocin expression, exacerbates microglial activation and impairs myelination. A long‐lasting oxytocin receptor agonist regulates microglial reactivity and confers long‐term neuroprotection.